PEMBERDAYAAN MASYARAKAT MELALUI PELATIHAN MUSIK TERBANGAN PADA KELOMPOK MUSIK TERBANGAN MUSLIMAT NU KECAMATAN JATEN KABUPATEN KARANGANYAR - Teti Darlenis (Institut Seni Indonesia Surakarta, 2020)
NU’ Ts erbangan Music Art Group in the Jaten Subdistrict of Karanganyar Regency is widely used for various purposes, such as celebrations, recitals, both public and commemorating Islamic holidays. The members consist of mothers who are members of the Muslimat recitation group NU District of Jaten. Problems encountered were that there were no trainers, no single vocals, and exercises that were not regularly scheduled. The results of the training in the form of the enthusiasm of the trainees are very high so that discipline of practice can be maintained; trainees are getting smarter in beating Terbangan instruments properly and being able to play a musical instrument playing pattern; and the music vocalist Terbangan can voice vocal songs correctly.Keywords: training, open music, NU, Jaten,